2017
DOI: 10.1111/1365-2745.12905
|View full text |Cite
|
Sign up to set email alerts
|

Cereal progenitors differ in stand harvest characteristics from related wild grasses

Abstract: The domestication of crops in the Fertile Crescent began approximately 10,000 years ago indicating a change from a hunter‐gatherer lifestyle to a sedentary, agriculture‐based existence. The exploitation of wild plants changed during this transition, such that a small number of crops were domesticated from the broader range of species gathered from the wild. However, the reasons for this change are unclear.Previous studies have shown unexpectedly that crop progenitors are not consistently higher yielding than r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 62 publications
(88 reference statements)
0
13
1
Order By: Relevance
“…Our research clarified the evolutionary relationships between the direct wild relatives of cultivated Arabica coffee, providing a strong instrument for the selection of wild plant species in coffee breeding programs. The closest relatives of a crop often contain more favorable characteristics for breeding than distantly related species, showing the importance of phylogenetic studies on crop wild relatives for crop improvement (Preece et al, 2015(Preece et al, , 2018Martín-Robles et al, 2019…”
Section: Discussionmentioning
confidence: 99%
“…Our research clarified the evolutionary relationships between the direct wild relatives of cultivated Arabica coffee, providing a strong instrument for the selection of wild plant species in coffee breeding programs. The closest relatives of a crop often contain more favorable characteristics for breeding than distantly related species, showing the importance of phylogenetic studies on crop wild relatives for crop improvement (Preece et al, 2015(Preece et al, , 2018Martín-Robles et al, 2019…”
Section: Discussionmentioning
confidence: 99%
“…However, archeobotanical evidence indicates that small-seeded grasses were an (arguably more) important source of food for pre-agricultural groups (Savard et al, 2006;. Furthermore, earlier experiments have shown that large-seeded grass and legume progenitor species are not necessarily higher yielding than smaller-seeded species in the same families (Preece et al, 2015(Preece et al, , 2018.…”
Section: Seedling Growth Potentialmentioning
confidence: 99%
“…However, although domesticated cereals of the Fertile Crescent have a greater potential yield than their wild progenitors (Preece et al, 2017), the wild progenitors do not consistently produce a higher yield than other wild grasses available in the region before and during the transition to agriculture (Preece et al, 2015(Preece et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations